Modulation of chlorophyll concentration by downwelling Rossby waves during the winter monsoon in the southeastern Arabian Sea. (July 2020) - Amol, P.; Bemal, Suchandan; Shankar, D.; Jain, V.; Thushara, V.; Vijith, V.; Vinayachandran, P.N.
Highlights: Chlorophyll variability driven by horizontal advection in southeastern Arabian Sea. The horizontal advection is associated with Rossby wave propagation. Region around Sri Lanka and the Maldives acts as source of nutrients. Impact of Rossby wave evident in oxygen, water mass, and nutrient distribution. Vertical processes are weak except along coasts and around islands. Abstract: Signatures of Rossby waves that are evident in satellite ocean colour data in the southeastern Arabian Sea (SEAS) are more prominent during the winter than the summer monsoon. During the winter, the sea level is high, and the conditions are less conducive for the injection of nutrients through the eddy-pumping mechanism. In this study, we use satellite observations and a physical-ecosystem model to examine the role of horizontal advection associated with Rossby waves in enhancing chlorophyll concentration in the SEAS. Zonal advection dominates over meridional advection, and its effect is more prominent in the south of Indian subcontinent and west of the Maldives. Except along the coast and around the islands, the vertical processes are weak and do not lead to a substantial increase in chlorophyll. Model simulations show that the currents associated with the Rossby wave also transport nutrients and other physicochemical properties of water along the path of the wave. The advected water decreases the concentration of Arabian Sea High Salinity water mass and replenishes the oxygen in the oxygen minimum zone in the SEAS.